Looking Beyond Institutional Boundaries: Examining Adults’ Experience of Choosing Online as Part of Their Post-Secondary Studies - Rasmussen, Kari (International Review of Research in Open and Distributed Learning, 2018)
This research focused beyond the student, course, program, or institution by examining the conceptions of adults at the moment in time that they evaluated their choice to engage in furthering their post-secondary education by examining the possibilities provided through online learning. To capture their experience, not as students but as members of society, a practice of care framework, adapted from Tronto’s (1993) work, was utilized as a theoretical framework.  The use of this framework acknowledges that the practice of care is present in the lives of every human being and that each human being has received and/or provided care as part of their lived experience. A phenomenographical qualitative approach was the basis for the design of this project which allowed for the identification of the commonalities and variations of the described experience.  All described experiences illustrated the balancing of needs, wants, and responsibilities, these descriptions included recognition of care of one’s self, one’s family, and one’s community. The variation could be described as an expansion of the recognition of care, that is the focus of care expanded from self to family and then from family to community. This expansion occurred only in those described experiences that showed a strong conception of themselves within the previous category. The findings show that the choice to access online courses and/or programs provides possibilities for many adults that wish to continue their education but only if the educational environment can move away from its institutional centric perspective.